Relazioni tra progetto e manutenzione delle componenti vegetali in un giardino storico. Il parco del Neto a Calenzano (Firenze) - Martelli, Silvia (Ri-Vista. Research for landscape architecture, 2015)
This note about the meaning of conservation of vegetable elements in historical gardens, driver us to an interpretation of the role of routine maintenance in the delicate restoration process. Plants are part of the biological cycle of birth, growth and death, so the need continuous growing cares that has times longer than a normal restoration work. For this reason the routine maintenance has to be part of an unitary restoration plan that drives also the easier works, in a conscious way.